Fresh off the boat. The complete fifth season [videorecording (DVD)] - Wu, Constance, 1982-; Park, Randall; Yang, Hudson, 2003-; Wheeler, Forrest, 2004-; Soong, Lucille, 1938-; Chen, Ian, 2006-; Huang, Eddie (20th Century Fox Home Entertainment, 2019)
The Huangs find themselves navigating new waters as they grow up in - and possibly away from - 90's suburban Orlando. Dad Louis is now not only focused on his growing business, but his growing kids before they scatter with lives of their own. With the release of her mystery/thriller novel, mom is looking toward the next chapter in her life - all while her beloved Evan continues to help her maximize efficiency during weekly CostCo trips. Charmed, carefree middle child Emery continues to do well at everything, but realizes his co-dependence on his baby brother may be ending when they ditch their bunk beds. And with his best friend Nicole moving to New York, teenager Eddie begins to think about his own future, his ultimate independence away from the family - and possibly a two-week Chinese-American cultural exchange program dubbed "The Love Boat."